CO2 methanation process synthesis by superstructure optimization. Issue 40 (September 2020) - Uebbing, Jennifer; Rihko-Struckmann, Liisa; Sager, Sebastian; Sundmacher, Kai
Highlights: Superstructure covering 13 alternative technologies for power-to-methane processes. Global optimization with respect to multiple objectives. Over 600 potential process routes. Simultaneous optimization of indirect heat integration via a heat exchanger network. Identification of the effect of the selected electrolyzer and methanation technology. Abstract: A superstructure optimization approach to power-to-methane process design that includes heat integration is presented. Carbon dioxide from biogas plants is considered as carbon source. The superstructure includes 13 alternative process technologies in seven layers for power-to-methane processes at their current stage of development. For different scenarios, the most efficient process in terms of product chemical exergy and the most cost-effective process in terms of capital and total annual costs are identified. We consider indirect heat integration via utilities, which for all scenarios, is determined to be a main contributor to both energy efficiency and process cost. The product methane must meet the requirements for feed into the gas grid. The requirements for the gas grid have a direct influence on the most efficient process route. The number of necessary process units is reduced, if hydrogen can be fed to the gas grid. Furthermore, extend of the heat exchanger network determines the trade-off between efficiency and costs, rather than choice of unit operations.